Anatomical Diseases Caused by Congenital Duodenal Abnormalities - Yu Jin Kim; Heung Up Kim (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Disorders of duodenal anatomy are rare and originate during the early embryological development of the foregut. These disorders are associated with significant morbidity in children; however, they may remain undetected during childhood and present during adolescence or adulthood. Duodenal atresia or web, annular pancreas, Ladd’s bands associated with midgut volvulus, and preduodenal portal vein represent duodenal anomalies that may cause partial or complete duodenal obstruction. Duodenal atresia and web occur secondary to incomplete recanalization of the duodenal lumen during the 8th to 10th week of gestation. These anomalies usually require surgical correction; however, the role of endoscopic interventions using innovative equipment is being investigated. Duodenal duplication cysts are an extremely rare congenital anomaly. Most abut the second or third portion of the duodenum and histologically show the normal duodenal wall layers. These lesions clinically present with abdominal pain, weight loss, vomiting, pancreatitis, or features of biliary tract obstruction. Imaging studies including transabdominal ultrasonography, computed tomography, MRI, and endoscopic ultrasonography are useful for detection of the cystic structure. Surgery is the conventional therapeutic modality used for management of duodenal duplication cysts; however, marsupialization (endoscopic intervention to establish communication between the cyst cavity and the duodenal lumen to facilitate duodenal drainage of cystic contents) is increasingly being performed in clinical practice. Duodenum inversum and duodenal diverticula are congenital duodenal disorders that require endoscopic or surgical management in symptomatic patients.